Scalable Manufacturing of Mechanical Robust Bioinspired Ceramic-Resin Composites with Locally Tunable Heterogeneous Structures - Zhang, Zhen-Bang (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.